Recenzja przekładu traktatu agronomicznego "De agri cultura" Marka Porcjusza Katona autorstwa Ireneusza Mikołajczyka - Szafrańska-Sienkiewicz, Sylwia (Collectanea Philologica, 2011)
The author describes a new Polish translation of M.P. Catonis’ work De agri cultura, which was published in Toruń in 2009. Terms of a field of agriculture, medicine and technologies, appropriate translated and discussed in detail, are indicated as the values of this translation. According to author’s opinion, a style of the translation, which is accessible for a contemporary reader, deserves a recognition.